Pola Pencarian Data Investigasi di Media Online - Tika Rizkina Azizah; Septiawan Santana; Firmansyah (Bandung Conference Series: Journalism, 2021)
Abstract. In investigative journalism work, there are three general forms of investigative methods, namely, related to the work of investigating documents, as well as investigations of individual subjects related to the problem. This general form of investigative reportage is termed a paper trail, people trail, and money trail. Tempo Magazine is a media that is considered to have competence and credibility for investigative coverage. Tempo magazine is a pioneer of investigative journalism in the period after 1990. In addition, the internet media has opened up information expansion based on a multidimensional "network". A number of platforms on the internet have emerged that can attract people's attention. Like it or not, the print media must also adapt their work to the needs of the public. In the end, the print media also experienced convergence. In the world of journalism, online journalism was born. This study aims to determine why and how investigative data search patterns in online media. This study uses a qualitative method with a case study approach. In this case the researcher tried to find out the pattern of investigative data collection in the online media through investigative news entitled "Pesta Terakhir Aktivis Ambon" conducted by Tempo.co and investigative news entitled "Emas Hitam Mahakam dalam Bidikan KPK" conducted by Katadata.co.id . The result of this research is that investigative journalism work in online media is basically the same as investigative journalism work in print media. The only difference is that there are more readers in online media. Especially in reporting done on online media, the writer can add digital content that can help explain this information. Abstrak. Dalam kerja jurnalisme investigasi, terdapat tiga bentuk umum metode investigasi yaitu, terkait dengan pekerjaan menginvestigasi dokumen-dokumen, serta penyelidikan terhadap subjek-subjek individu yang terkait dengan permasalahan. Bentuk bidang umum reportase investigasi ini diistilahkan dengan paper trail, people trail, dan money trail. Majalah Tempo menjadi media yang dinilai memiliki kompetensi dan kredibilitas untuk peliputan investigatif. Majalah Tempo merupakan pelopor jurnalisme investigatif di masa setelah 1990. Disamping itu media internet membuka perluasan informasi berdasarkan “jaringan” yang multidimensi. Sejumlah platform di internet muncul yang dapat menarik perhatian masyarakat. Mau tidak mau media cetak juga harus menyesuaikan pengerjaannya dengan kebutuhan publik. Pada akhirnya media cetak pun mengalami konvergensi. Dalam dunia jurnalistik maka lahirlah Jurnalisme Online. Penelitian ini bertujuan untuk mengetahui mengapa dan bagaimana pola pencarian data investigasi di Media Online. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Dalam hal ini peneliti berusaha mencari tahu pola pengumpulan data investigasi di media online melalui berita investigatif berjudul “Pesta Terakhir Aktivis Ambon” yang dilakukan oleh Tempo.co dan berita investigatif berjudul “Emas Hitam Mahakam Dalam Bidikan KPK” yang dilakukan oleh Katadata.co.id. Hasil dari penelitian ini adalah kerja jurnalisme investigasi di media online pada dasarnya sama dengan kerja jurnalisme investigasi di media cetak. Yang membedakan hanya pada pasar pembaca di media online lebih banyak. Terlebih dalam pelaporan yang dilakukan pada media online penulis dapat menambahkan konten digital yang dapat membantu menjelaskan informasi tersebut.